Visual impact assessment of wind turbines and their farms on landscape of Kretinga region (Lithuania) and Grobina townscape (Latvia) - Abromas, Jonas; Kamičaitytė-Virbašienė, Jūratė; Ziemeļniece, Aija (Journal of Environmental Engineering and Landscape Management, 2015)
Early in 2013 as many as 5 wind farms were in operation in Kretinga region and the sixth was under construction. The wind farms are concentrated within two territories, i.e. in the south-west part of the region (between Kretinga and Palanga towns) and in the north-west (between Darbėnai and the Senoji Įpiltis villages). The region also houses seven individual wind turbines, the total number being 58 units. In seeking to assess the impact of wind turbines based in Kretinga region on the landscape and the villages, the analysis of cartography material was carried out and the inventory of all wind turbines was made (GIS data base). On assessing the importance of the roads with regard to the intensity of traffic and tourist flows, the observation places were established and photo fixation was performed. The impact was assessed from eleven observation places (all the places were close to the roads). During the study, the nature, importance and degree of contrast of the visual impact of wind turbines were assessed. In assessing the visual impact of wind turbines on the landscape, it was found that woodlands and villages make a significant impact on the visibility of turbines. The wind turbines seen on the axis of the road perspective are not only observed for some length of time, but often serve as a landmark. The investigation results were compared with the situation in western Latvia region (Grobina case).First published online: 03 Jul 2014